NIMG-15. INTEGRATED RADIOGRAPHIC AND PATHOLOGICAL ANALYSIS OF MALIGNANT PERIPHERAL NERVE SHEATH TUMORS (MPNSTS) REVEALS IMAGING CORRELATES OF MOLECULAR ALTERATIONS AND CLINICAL OUTCOME. (14th November 2022) - Diwanji, Devan; Texiera, Stephanie; Lucas, Calixto-Hope; Calabrese, Evan; Reddy, Alyssa; Pekmezci, Melike; Jacques, Line; Chin, Cynthia; Vasudevan, Harish
Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are the most common cause of death in patients with neurofibromatosis type 1 (NF-1) yet non-invasive diagnosis and risk stratification of NF-1-associated peripheral nerve tumors remains challenging. Moreover, the relationship between radiographic features and pathologic measures such as mitotic index and necrosis, or molecular markers of malignant transformation such as H3K27 trimethylation and Schwann cell marker (S100B, SOX10) expression remain unknown. Here, we integrate positron emission tomography (PET) (n=32 studies from 18 patients) and magnetic resonance imaging (MRI) (n=20 studies from 20 patients) with immunohistochemical analysis and clinical follow-up in a total of 20 patients with pathologically confirmed MPNST diagnosis. The median age was 33 years (range 5-74 years), n = 11 were male (55%) and n=13 (65%) harbored a clinical diagnosis of NF-1. Anatomically, n=6 (30%) tumors arose near the spine, n=5 (25%) arose in the extremities, and n=4 (20%) arose in the sacrum. By PET, the average preoperative SUVmax was 8.53 with a trend toward increased SUVmax in Ki-67 high tumors (SUVmax 10.58 vs. 6.47, p=0.08). No significant differences in SUVmax based on H3K27 trimethylation, SOX10, or S100B expression was noted. The appearance of cystic necrosis by MRI was significantly associated with H3K27 trimethylation loss (Chi-square p=0.04) with a trend toward increased KI-67 labeling (43% vs. 24%, p = 0.07), suggesting cystic necrosis identifies aggressive lesions. No other features were correlated with H3K27 trimethylation status or Ki-67 labeling index. With regard to clinical outcome, dichotomized SUVmax identified patient subgroups with significant differences in overall survival (OS), with high SUVmax tumors demonstrating improved survival (median OS: 250 months vs. 60 months, log-rank test p=0.02). Our data support a relationship between radiographic features, histopathologic characteristics and clinical outcomes. Future work will include longitudinal analysis, validation in larger, multi-institutional cohorts and incorporation of radiomic approaches.